Leptospira interrogans Sensu Lato in Wild Small Mammals in Three Moravian Localities of the Czech Republic - Žákovská, Alena; Treml, František; Nejezchlebová, Helena; Nepeřený, Jiří; Budíková, Marie; Bártová, Eva (Pathogens (Basel, Switzerland), 2022)
Leptospirosis is a widespread zoonosis, affecting humans, domestic animals and wildlife, with small mammals as a reservoir of this infection. In recent years, this disease has been re-emerging and affects approximately 1 million people all over the world each year. Due to this disease having a significant health impact, it is important to identify the source and method of infection. The risk of Leptospira sp. infection is higher mainly in the cities of developed and industrialised countries. The aim of the study was the detection of antibodies against Leptospira sp. in some wild small mammals captured in the Czech Republic. In total, samples of 855 animals captured in three locations of Moravia during a six-year study (2010-2015) were examined by a microscopic agglutination test, using eight serovars of Leptospira interrogans sensu lato, representing serogroups Grippotyphosa, Icterohaemorrhagiae, Australis, Canicola, Sejroe, Javanica, Pomona and Pyrogenes, as antigens. Antibodies to Leptospira sp. were detected in 6.1% (52/855) of animals, with a prevalence of 6.4% (51/801) and 1.9% (1/54) in rodents and insectivores, respectively. The only statistically significant difference (p ≤ 0.05) was in prevalence between individual species (0-33%), while there were no differences in sex (6.7% in females and 5.1% in males), locality (1.8-8%) and year of trapping (0-8.4%). Only two serovars, L. interrogans serovar Pomona and L. interrogans serovar Grippotyphosa, were detected in 5.5% and 0.5% of animals, respectively. The prevailing serovar of pathogenic L. interrogans s.l. can be identified in a number of infected people in the Czech Republic. The composition of vaccines should be based on the current occurrence of Leptospira serovars in the actual territory. For this reason, the occurrence of Leptospira and its serovars should therefore be regularly monitored.
Keywords: leptospirosis; seroprevalence; incidence; rodents; Apodemus flavicollis